Evaluasi Pengalaman Pengguna Pada Aplikasi E-Wallet OVO dan GOPAY Dengan Metode User Experience Questionnaire - Fara Della Nur Annisa; Joy Nashar Utama Jaya; Surmiati Surmiati (Journal of Information System Research (JOSH), 2022)
Indonesian smartphone users are growing every year, so application developers continue to innovate to create non-cash payment services to make it easier for users to make non-cash transaction payments. There are currently many digital wallet applications, but ovo and gopay apps are common. The study is to compare the 2 digital wallet applications that have a business process and similar characteristics in both the user experience of the digital wallet application and want to know which user corresponds with both of the comfort, function and convenience of the customer in using one of the e-wallet support applications. The study gives a comparison through the user experience questionnaire (ueq) who has six assessments between attractiactiveness, spicdialing, seduction, dependent, stimulation, and stimulation. The UEQ questionnaire was divide to 85 respondents, as the result from the UEQ questionnaire indicates that the respondents had a positive impression on both ovo and gopay digital wallet applications Where the application shows positive (values mean > 0.8).